Analisis Produktivitas Pekerja Wanita Etnis Bugis, Makassar Dan Toraja Pada Sektor Industri DI Kota Makassar Sulawesi Selatan ( STUDI PADA INDUSTRI MAKANAN MINUMAN) - Aryati Arfah ; Prof.Dr. Pudjihardjo. SE.,Ms, Dr. Khusnul Ashar, SE.,MA, Dr. Susilo, SE.,MS (Disertasi Ilmu Ekonomi FEB-UB, 2011)
This research aims to test and prove empirically: (1) whether individual characteristics (health, tenure, work ethics), demographic factors (age, number of dependents), social-economic characteristics (education, wage), work environment and government regulations have any impact on the productivity of female workers from the Buginese, Makassarese and Torajan ethnic groups in the sectors of small, mid-sized and large industries in the municipality of Makassar